THE STATE AND TERRORISM - Ryszard JAKUBCZAK (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
Facing the current banking crisis which can be described as a confrontation between governing powers, private banks enjoying political and legal privileges and the rest of the society, the issue of international terrorism seems to be less attractive for the mass media. Bad economic results in the countries of western civilization were caused by reckless activities of big national companies and speculative capital rather than by terrorism. In recent years all western countries have been engaged in the fight against terrorism, there is no government which would not address the threat of terrorism in its security strategy. Moreover, many countries wrote long chapters devoted entirely to action plans counteracting terrorism. Terrorism is not an extraordinary phenomenon characteristic only for the contemporary times. It has a tradition which is centuries long – the only difference is that today we have wide access to information via mass media, it is so much easier to spread the word. Terrorism should be treated as a political phenomenon and as a consequence of exercising power in a certain way. This phenomenon affects security understood in global, national and regional sense. On all levels it has similar effects. Last but not least, it has an impact on the defence of international structures, in particular of national nature. At the moment Poland is not in a position to guarantee security of its territory by military means and is not capable to conduct anti-terrorist operations in case of necessity.